ENSURING THE BUDGET SECURITY OF UKRAINE DURING THE CRISIS THROUGH STRENGTHENING OF FISCAL STABILITY - Samorodov, Borys; Galych, Roman; Miroshnyk, Oleksii (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2022)
In order to ensure sustainable economic growth, Ukraine, like many other countries of the world, sets the main task of carrying out a comprehensive socio-economic reform. At the same time, factors that prevent the effectiveness of its implementation pose a threat to financial security due to the loss of stability of its components. Such multifaceted factors include the spread of globalization and digitalization processes, which, along with new opportunities, create new challenges and threats, which, in turn, require a reliable economic foundation and support for financial stability, the formation of centralized funds and the attraction of long-term financial resources. An important tool, along with others, is the budget policy, which combines the regulatory and fiscal functions of the organization of the budget process, optimally and continuously through budget expenditures supports the creation of a resource for the leveling of threats and the development of the economy, and the indicator of its effectiveness is budgetary security. Therefore, the unsolved problematic issues of ensuring budget security as a strategic direction of financial security, in the relationship and mutual influence with fiscal stability, determined the choice of the research topic, its purpose and tasks. the impact of fiscal stability on it requires further research. The object of the study is the process of ensuring budgetary security. The subject of the research is theoretical, methodical and applied aspects of fiscal stability as a factor influencing budget security. The purpose and task of the study is to generalize and systematize the theoretical foundations and methodological approaches of ensuring budgetary security, impact assessment and development of proposals for strengthening budgetary security through the improvement of budgetary and fiscal policy, strengthening fiscal sustainability. To achieve the set goal, the research implemented the following tasks: generalized the theoretical principles of budget security; the role and significance of fiscal policy and fiscal sustainability in ensuring budget security are characterized; diagnosis of the state of budget security of Ukraine was carried out; the level of fiscal stability was analyzed and its impact on the budgetary security of Ukraine was assessed; practical recommendations have been developed to strengthen budget security through strengthening fiscal sustainability.